A current-value Hamiltonian approach to discrete-time optimal control problems in economic growth theory. Issue 1 (2nd January 2022) - Naz, R.
Abstract : The Pontryagin-type maximum principle (PMP) is extended to the present and current-value Hamiltonian systems of nonlinear ordinary difference equations (NODFEs) for the uniform time step h . A new method termed as a discrete-time current-value Hamiltonian method is established for the construction of first integrals for current-value Hamiltonian (CVH) systems of NODFEs arising in Economic growth theory.